






1a. 
X • 0 = 0 

1b. 
X + 1 = 1 

Annulment Law 
2a. 
X • 1 = X 

2b. 
X + 0 = X 

Identity Law 
3a. 
X • X = X 

3b. 
X + X = X 

Idempotent Law 
4a. 
X • X = 0 

4b. 
X + X = 1 

Compliment Law 
5. 
= X 
Involution Law 
6a. 
X • Y = Y • X 

6b. 
X + Y = Y + X 

Commutative Law 
7a. 
X (Y Z) = (X Y) Z = (X Z) Y = X Y Z 
Associative Law 
7b. 
X + (Y + Z) = (X + Y) + Z = (X + Z) + Y = X + Y + Z 
Associative Law 
8a. 
X • (Y + Z) = X Y + X Z 

8b. 
X + Y Z = (X + Y) • (X + Z) 

Distributive Law 
9a. 
X • Y = X + Y 

9b. 
X + Y = X • Y 

de Morgan's Theorem 
10a. 
X • (X + Y) = X 

10b. 
X + X Y = X 

Absorption Law 
11a. 
(X + Y) • (X + Y) = X 

11b. 
X Y + X Y = X 

Redundancy Law 
12a. 
(X + Y) • Y = XY 

12b. 
X Y + Y = X + Y 

Redundancy Law 
13a. 
(X + Y) • (X + Z) • (Y + Z) = (X + Y) • (X + Z) 
Consensus Law 
13b. 
X Y + X Z + Y Z = X Y + X Z 
Consensus Law 
14a. 
X ⊕ Y = (X + Y) • (X + Y) 

14b. 
X ⊕ Y = X Y + X Y 

XOR Gate 
14c. 
X ⊕ Y = (X • Y) • (X + Y) 




XOR Gate (14a + 9a) 
15a. 
X ⊙ Y = (X + Y) • (X + Y) 

15b. 
X ⊙ Y = X Y + X Y 

XNOR Gate 

X ⊙ Y = X ⊕ Y 

15c. 
X ⊙ Y = X + Y + X Y 

XNOR Gate (15b + 9b) 